Stones, bones, and antler tines : a comparison of midwest arrow points - Jordan, Jamison (My University, 2013)
Cultures in the Midwest such as the Mississippian and Oneota crafted projectiles from raw materials ranging from local stone to exotic materials, bone and antler. This thesis is a study of differences in the nature of raw materials, as well as the advantages and disadvantages of each. Methods were employed to measure time invested in manufacturing and hafting each projectile point, as well as how each point performed when used against a target. As a result, this thesis was able to better understand the properties of each type, possibly determining the use of each. In general, stone points had the lowest cost of time to create, however, organic points required less skill. In terms of performance, the wounds caused by lithic points and distal phalanges are suitable for harvesting medium and large game, while antler tine points are effective against both medium and small game.
Keywords: Middle West -- Antiquities.; Oneota Indians -- Antiquities.; Mississippian culture -- Middle West.; Archaeology -- Methodology.; Natural products.